Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1002/qj.49709440207
|View full text |Cite
|
Sign up to set email alerts
|

The spectra of charging events due to the collision of natural ice particles with an ice surface

Abstract: SUMMARYA sensitive, solid state electrometer has been built which is capable of measuring the individual charges acquired by an ice surface exposed to precipitation or cloud particles. Measurements made in natural snowfall show that the individual charges fluctuate widely both in sign and magnitude. Individual charges ranging frome.s.u. have been recorded within an interval of a few seconds. In most cases the ice surface received a net positive charge, and the median charge per collision was about 2 x lo-' e.s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The force of the collision between the particles and roughness of the ice surfaces are also factors. Scott and Hobbs (1968) showed that the sign of the charge acquired by an ice specimen from a collision depends on the shapes of the particles involved and the magnitude of the charge acquired increases with increased impact velocities. Latham and Stow (1965) found that charge transfer associated with the thermoelectric effect could be greatly enhanced if the ice specimens are rough and if impact velocities are high.…”
Section: Electrification In Blizzardsmentioning
confidence: 99%
“…The force of the collision between the particles and roughness of the ice surfaces are also factors. Scott and Hobbs (1968) showed that the sign of the charge acquired by an ice specimen from a collision depends on the shapes of the particles involved and the magnitude of the charge acquired increases with increased impact velocities. Latham and Stow (1965) found that charge transfer associated with the thermoelectric effect could be greatly enhanced if the ice specimens are rough and if impact velocities are high.…”
Section: Electrification In Blizzardsmentioning
confidence: 99%
“…Collision or riming give rise to these processes [Latham and Mason, 1961b;Scott and Hobbs, 1968;Hallett and Saunders, 1979]. The charge carried off by ejected splinters or secondary crystals may have been generated at the newly created surface, or it may have been present before splintering in the form of surface electrons, induced charge, or as the result of thermal or concentration gradients.…”
Section: Splintering and Secondary Crystal Productionmentioning
confidence: 99%
“…Superposed on the three previous mechanisms are the charge separation effects due to splintering, or secondary crystal production, and to inductive polarization by an external field. Depending on strength and sign of the latter, separation of inductively polarized charge by colliding particles may enhance or reduce charge separation by other processes [e.g., Buser, 1976]; it may become dominant [Shewchuk and Iribarne, 1974] and then determine the sign of overall charge separation [Hobbs and Burrows, 1966;Burrows et al, 1967;Scott and Hobbs, 1968;Pruppacher and Klett, 1978, pp. 601-605].…”
Section: Collision Mechanisms In Perspectivementioning
confidence: 99%